Penerapan Model Make A Match untuk Meningkatkan Pemahaman Konsep Nilai Tempat (Puluhan dan Satuan) Siswa Kelas II di SDN Cipete 4 - Fadhillah Dwi Indriani; Cahaya Suci Ramadhania; Adinda Nazwa Kharisma; Rifka Nur Rahmadani; Putri Kholifah; Mawardi (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
Understanding the concept of place value is an essential foundation for learning mathematics in elementary schools. However, second-grade students at SDN Cipete 4 still experience difficulties in understanding the concepts of units, tens, comparing, and ordering numbers. This study aims to improve understanding of the concept of place value through the application of the Make-A-Match learning model. This study used the Classroom Action Research (CAR) method, implemented in two cycles, each consisting of planning, implementation, observation, and reflection. The research subjects were second-grade students at SDN Cipete 4. Data collection techniques included tests, observation, and documentation. The results showed that the application of the Make-A-Match model improved students' understanding of the concept of place value, as indicated by an increase in average scores and the percentage of students' learning completion in each cycle. Therefore, the Make-A-Match model is effective in mathematics learning, particularly in place value. Keywords: Make-A-Match, place value, tens and ones, elementary mathematics.   Abstrak Pemahaman konsep nilai tempat merupakan dasar penting dalam pembelajaran matematika di sekolah dasar. Namun, siswa kelas II SDN Cipete 4 masih mengalami kesulitan dalam memahami konsep satuan, puluhan, membandingkan dan Menyusun bilangan. Penelitian ini bertujuan untuk meningkatkan pemahaman konsep nilai tempat melalui penerapan model pembelajaran Make A Match. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus, masing-masing terdiri atas perencanaan, pelaksanaan, observasi dan refleksi. Subjek penelitian Adalah siswa kelas II SDN Cipete 4. Teknik pengumpulan data meliputi tes, observasi dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan model Make A Match dapat meningkatkan pemahaman konsep nilai tempat siswa, ditunjukkan dengan peningkatan nilai rata-rata dan persentase ketuntasan belajar siswa pada setiap siklus. Dengan demikan model Make A Match efektif digunakan dalam pembelajaran matematika khusunya materi nilai tempat. Kata-kunci : Make A Match, nilai tempat, puluhan dan satuan, matematika SD.